Reduced Atmospheric Ion Escape Above Martian Crustal Magnetic Fields. Issue 21 (8th November 2019) - Fan, Kai; Fraenz, Markus; Wei, Yong; Han, Qianqian; Dubinin, Eduard; Cui, Jun; Chai, Lihui; Rong, Zhaojin; Zhong, Jun; Wan, Weixing; Mcfadden, James; Connerney, J.E.P.
Abstract: Martian crustal fields were considered as too weak to have a distinctive effect on global escape rates of Martian heavy ions. However, new observations by the Mars Atmosphere and Volatile Evolution mission reveal a more precise result and show a notably lower atmospheric ion escape region above the area of the strongest crustal fields. A comparison between the fluxes of high and low energy O + ions suggests that the strongest crustal fields may trap low energy ions and reduce the solar wind pick‐up efficiency while high energy ions form a flux depletion above the crustal field. Statistical results indicate a maximum reduction of the global escape flux by nearly 35% when the strongest crustal field region is oriented sunward. This is the first time that the protective effect of the crustal fields on heavy planetary ions has been observed and it might indicate a more effective protection of atmospheres by stronger magnetic fields like at Earth. Plain Language Summary: The disappearance of liquid water on Mars is frequently understood as a consequence of enhanced atmospheric escape due to a lack of Earth‐like dipole magnetic fields to protect its atmospheres from erosion by the solar wind. However, this hypothesis does not have a lot of supporting evidence. The Mars Atmosphere and Volatile Evolution mission for the first time observes an area of lower outflow of high energy O + ions above the region of the strongest crustal magnetic fields on the Martian southern hemisphere. Four years of statistical results show that up to 35% of O + ions do not escape when the strongest crustal magnetic fields are facing toward the Sun. Our results suggest that the crustal magnetic field is crucial for ion escape processes and may significantly affect the evolution of the Martian atmosphere. Key Points: We report the first observation of the protective effect of the Martian crustal field on dayside O + ions The outward fluxes of O + ions linearly decrease as altitude decreases and crustal magnetic field increases on the Martian dayside The reduction of outward fluxes reaches a maximum of 35% when the strongest crustal field is sunward